The Impact of COVID-19 on Learning: Investigating EFL Learners' Engagement in Online Courses in Saudi Arabia - Iman Oraif; Tariq Elyas (MDPI AG, 2021)
As a result of the COVID-19 pandemic, most learning around the world has been transferred online. Learners who previously engaged in traditional learning now face a new challenge, a distinctive rise in e-learning. This drastic change could impact their learning behavior and acceptance of the change. As a result, their learning engagement could be affected massively. The present study therefore explores learners' level of engagement in online courses using a designated school platform within the context of Saudi Arabia. A reliable measure was implemented in the study based on the Student Course Engagement Questionnaire (SCEQ). A survey was consequently conducted in a high school in Saudi Arabia, with a sample of 379 female English as a foreign language (EFL) learners studying a general English language course. The results revealed a high level of engagement among EFL Saudi learners. This helped to generate recommendations to improve EFL practices, primarily through the use of an online environment either at the national level in the Saudi context or the international level.